Restrictive business practices of multinational enterprises : report of the Committee of Experts on Restrictive Business Practices. - Organisation for Economic Co-operation and Development (Paris : Organisation of Economic Co-operation and Development (OECD), 1977)
The report focus on issues of competition policy and procedures relating to multinational enterprises in 19 member countries of the OECD. The report focused on definitional problems and short history of multinational enterprises; theoretical and empirical analysis of their extent and nature; the motive for their formation; and their pro- and anti-competitive effects.
Includes bibliographical references.
lje 11/05/2017
Loans
Keywords: International business enterprises; Restraint of trade; Patent licenses; Patent laws and legislation; United States; Europe; Canada